Perbedaan Lama Pelepasan Tali Pusat pada Bayi yang Dimandikan ke Dalam Air Hangat dengan Bayi yang Dilap Handuk Basah - Herman Herman; Mudrika Mudrika (Jurnal Keperawatan Silampari, 2022)
This study aims to determine the difference in the length of the umbilical cord detachment in babies bathed in warm water with babies who are wiped with a wet towel at Batara Siang Hospital, Kab. Pangkep. The research method used is quasi-experimental research (quasi-experimental) using the Experimental Design-Equivalent Time Sample method. The results showed that the average length of umbilical cord detachment for infants who were bathed in warm water (experimental group) was 110.8 hours or 4.97 days, while the average length of time for removing the umbilical cord of infants who were wiped with a wet towel (control group) was 76. ,9 hours or 6.6 days. The average difference between the two groups is 24.72 hours or 1.20 days. The results of the statistical test obtained a P-value (<0.001), meaning that at alpha 5%, there was a significant difference in the average length of umbilical cord detachment between babies who were wiped with a wet towel, which was 2.01 days and babies who were bathed in warm water, which was 4, 01 day. So that the care of babies who are wiped with a wet towel is more effective, and the umbilical cord is removed faster than the care of babies bathed in warm water. Conclusion: There is a significant difference between umbilical cord care and the average length of umbilical cord detachment between babies who are wiped with a wet towel and babies who are bathed in warm water. Keywords: Wet Wiping, Bathe, Leasing, Umbilical Cord